Niemann - Pick disease associated with hemophagocytic syndrome - Serap Karaman; Nafiye Urgancı; Günsel Kutluk; Feyzullah Çetinkaya (Turkish Journal of Hematology, 2010)
Hemophagocytic lymphohistiocytosis (HLH) is a disease characterized by phagocytosis of blood cells by macrophages within the lymphoreticular tissue. It can develop secondary to some diseases or be familial as a result of genetic mutations. Niemann-Pick disease (NPD) is a very rare lipid storage disease. A three-month-old girl presented with high fever (39°C), abdominal distension and paleness. The parents were consanguineous. The liver and spleen were palpable 10 cm and 11 cm below the costal margins, respectively. Bicytopenia (Hb: 5.5 g/dl, platelet: 77000/mm3), hypertriglyceridemia (351 mg/dl), hyperferritinemia (>1500 ng/dl) and hypofibrinogenemia (120 mg/dl) were detected. Bone marrow aspiration demonstrated foam cells and hemophagocytosis by macrophages and Niemann-Pick cells. Lysosomal sphingomyelinase activity was 0.24 nmol/h/mg/protein (normal: 0.86-2.8). Due to the parents’ refusal of further evaluation, the nature of HLH as primary or secondary could not be determined. To the best of our knowledge, this is the first case of NPD associated with HLH and the first demonstration of hemophagocytosis by Niemann-Pick cells.